METALINGUISTIC AWARENESS OF MULTILINGUAL FIRST GRADERS: AN EXPLORATORY STUDY - Dalona, Irish Mae; Dalona, Alvert Dael (Universitas Ahmad Dahlan, 2019)
This study, which utilized a modified metalinguistic awareness test adopted from Dita?s (2009), probed on young children?s metalinguistic awareness in identifying syntactic errors; determining sounds and the use of phonological segments; and explaining a word on their own by describing its appearance or its functions in English, Filipino, and Cebuano. This study attempted to elucidate young children?s readiness to take on more difficult linguistic tasks in the succeeding academic levels. Since the children?s level of metalinguistic awareness is average, this study recommends that schools are encouraged to provide strategies and lessons that would enhance learners? metalinguistic awareness, most especially in terms of language arbitrariness in English and Filipino; and since there is significant difference in all three languages in all tests, parents and teachers should ensure that the pupils achieve full proficiency in all three languages by providing rich experiences equally in these languages.